Exploring the relationship between adults' perceptions of sedentary behaviours and psychological stress: Is your mindset stressing you out?. Issue 4 (4th July 2022) - Sick, Kelsey; Rollo, Scott; Prapavessis, Harry
ABSTRACT: Mindsets that people hold regarding activity adequacy play an integral part in various health outcomes. Yet, little is known about the relationship between the mindset one has about their sedentary behaviour levels and psychological stress. As such, the present study sought to understand if adults' perceptions of themselves as compared to others of the same age, specifically perceptions about their level of sedentary behaviours, is a significant predictor of psychological stress. Three-hundred and seventy-four adults ( n female  = 279, n male  = 95; M age  = 60.4% aged between 18 and 24) completed an online survey package that included two multi-scale instruments to assess perceived stress symptoms and actual time spent sitting during a typical week, and two single-items to measure perceptions of their level of sedentary behaviours during a typical week (i.e., typical weekday, weekend day). Cross-sectional results indicated that perceived sedentary behaviour relative to others on a typical weekend day explained significant albeit modest unique variance in perceived stress scores, even after controlling for covariates including actual sitting time on a typical weekend day ( t (363) = 2.35, p  = 0.019, R 2 increment  = 0.010). Weekday perceptions failed to be an influential factor ( t (363) = −0.28, p  = 0.780, R 2 inc  = .000). These findings suggest that a sedentary behaviour mindset, yoked within a social comparison framework, may be important for understanding psychological stress.